A Rare Manifestation of Chronic Gastric Ischemia With Ulceration - Gagan Verma; Joseph Mizrahi; Jela Bandovic; Lionel D'Souza (Annals of Internal Medicine: Clinical Cases)
We present the patient case of a woman with significant cardiovascular disease, chronic abdominal pain, and repeated episodes of gastrointestinal bleeding, who was ultimately diagnosed with chronic gastric ischemia with recurrent gastric ulcers. The current literature suggests that gastric ischemia is more common than previously thought. A higher degree of suspicion for this relatively rare presentation may be required in the clinical setting.